PENGELOLAAN SERANGGA-SERANGGA YANG BERASOSIASI DENGAN TANAMAN JAMBU METE - Soesanthy, Funny; Trisawa, Iwa Mara (Jurnal Tanaman Industri dan Penyegar, 2011)
Management of insects associated with cashew plant. Several kinds of insects associated with cashew plant. These insects are grouped intophytophagous insects, natural enemies (parasitoids and predators) and pollinators. Phytophagous Insects such as Helopeltis s pp., Sanurus indecora,Placoderus ferrugineus, Anastrepha fraterculus, and Cricula trifenestrata were reported become a constraint on the production of cashew in Indonesiaand several other countries. The natural enemies are egg parasitoid like Mesocomis orientalis, Trichogramma sp. and Aphanomerus sp, pupaeparasitoid like Brachymeria sp. and Tetrastichus sp. and adult parasitoids from family Epipyropidae, while predators like ants, Chilomenes lunataSphodromantis lineola, Tarachodes afzelii, and Amorphoscelis sp. In addition to natural enemies, the presence of insect pollinators such as Apismellifera and Centris tarsata are very important considering cashew require insect assistances for the formation of fruit. Knowledge of the complexassociations between insects and cashews need to know to their management strategies in the fields. Phytophagous insect management are directed toefforts at suppression their population by maximizing the role of natural enemies. Cashew ecosystem manipulation techniques s uch as management ofwild vegetation, pruning, and intercropping can be developed to encourage the role of natural enemies better. The technique is als o expected to attractpollinating insects visiting the cashew crop. In addition, actions that could disrupt the natural life such as the use of insecticides should be reduced.Insecticides are used only if the role of natural enemies was less successful and populations of phytophagous insects are at the level of adverse. Periodicmonitoring of insects associated with cashew nuts to be an important key to making subsequent decisions.